Transformational Leadership, Team Psychological Safety and Team Process Improvement: the mediating role of team psychological safety in the relationship between transformational leadership and team process improvement. - Gari, Federica Candida Lapiedra (2019)
Trabalho Final do Mestrado em Psicologia do Trabalho, das Organizações e dos Recursos Humanos apresentado à Faculdade de Psicologia e de Ciências da Educação